THE IMPACT OF GREEN ACCOUNTING IMPLEMENTATION ON THE PROFITABILITY OF FOOD AND BEVERAGE INDUSTRY SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN 2019-2023 - Polapa, Melisa Putri Sinto; Noholo, Sahmin; Husain, Siti Pratiwi (PT. Jurnal Center Indonesia Publisher, 2025)
This study aims to analyze the effect of green accounting implementation on the Company's profitability. This study was conducted on companies included in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2019-2023 period using a quantitative approach. Sample selection was carried out using the purposive sampling method, resulting in 80 observation data samples for five consecutive years. Data analysis techniques used include descriptive analysis using Microsoft Excel, hypothesis testing using SPSS 18 to test the effect of Green Accounting on Profitability. The results of this study indicate that Green Accounting has a negative and significant effect on Profitability.